Iris Recognition using Haar Wavelet Transform - Ibrahim, Ali Abdulmunim (Al-Nahrain Journal of Science, 2018)
Automatic iris recognition system is reliable for automatic personal identification. This research aims to recognize and identify iris among many that were stored in database. It is includes, after entered iris image, image preprocessing, feature extraction based on texture analysis using Haar Wavelet transform to capture both local and global features details in an iris and iris identification (matching process) based on the Euclidean distance between the new input iris and templates stored in the database then choose the minimum distance between them. So the score degree can determine the genuine or imposter person. The database can display information about any processed iris. The study conclusion that Haar wavelet transform was efficient distinguished and noise sensitive under different conditions.